Sparing Fish Oil with Soybean Oil in Feeds for White Seabass: Effects of Inclusion Rate and Soybean Oil Composition. (2nd April 2013) - Trushenski, Jesse; Mulligan, Bonnie; Jirsa, David; Drawbridge, Mark
Abstract: Fish oil sparing has proven difficult for some fish species, especially marine carnivores like White Seabass Atractoscion nobilis that require one or more long‐chain polyunsaturated fatty acids (LC‐PUFAs). Recent studies have suggested that the use of saturated fatty acid (SFA)–rich lipids instead of C18 polyunsaturated fatty acid–rich (C18 PUFA) lipids may be advantageous in maintaining tissue levels of LC‐PUFAs; SFA‐rich lipids may also offer a strategic advantage in terms of meeting the LC‐PUFA requirements of marine carnivores while minimizing dietary fish oil inclusion. Accordingly, we assessed the performance and tissue fatty acid composition of White Seabass (3.8 ± 0.2 g [mean ± SE]) fed diets containing fish oil or graded levels of C18 PUFA–rich standard soy oil or SFA‐rich hydrogenated soy oil (replacing 25, 50, 75, or 100% of dietary fish oil) for 8 weeks. Feed conversion ratio, weight gain, and specific growth rate were not impaired by partial or complete replacement of dietary fish oil with hydrogenated soy oil; however, fish oil sparing with standard soy oil was associated with declining performance. The tissue fatty acid profiles of fish fed the hydrogenated soy oil–based diets were very similar to those of fish fed the fish oil–based feed, but the standard soy oil–based feeds resulted in concomitant loss of n‐3 fatty acids and LC‐PUFAs. In all cases, the magnitude of the dietary effect was greater among liver and fillet tissues than among brain and eye tissues. These data suggest a limitation, potentially related to LC‐PUFA deficiency, associated with replacing fish oil with standard soybean oil, but not with hydrogenated soybean oil. Our data suggest that the LC‐PUFA requirements of White Seabass can be effectively reduced by feeding SFA‐rich alternative lipids, allowing for a greater level of fish oil sparing without growth impairment or tissue profile modification than is possible with C18 PUFA–rich lipids.